Renal vasodilator activity of prostaglandin E2 in the rat anaesthetized with pentobarbitone. - Haylor, J. (Nature Publishing Group, 1982)
1 The effect of intra-aortic administration (i.a.) of prostaglandin E2 (PGE2) on renal blood flow was studied in the rat anaesthetized with pentobarbitone. Renal blood flow was assessed in two ways, either by use of an electromagnetic flow probe or by measurement of the renal clearance of p-aminohippurate (PAH). 2 PGE2 (0.1 microgram/min, i.a.) increased renal blood flow measured by either method. However, PAH clearance overestimated the degree of vasodilatation compared to that obtained using the flow meter. The possibility that PGE2 or a metabolite may increase PAH extraction by the kidney was considered. 3 The sensitivity of the rat to the renal vasodilator actions of PGE2 was enhanced by using a flank retro-peritoneal approach from which to insert the flow probe, rather than a mid-line abdominal incision. 4 Dose-response curves demonstrate that under the conditions used, PGE2 produced a biphasic change in renal vascular resistance, vasodilatation started at 0.01 microgram/min and was maximal at about 3 micrograms/min, while at the highest dose used (20 micrograms/min) PGE2 induced renal vasoconstriction. 5 The results indicate that contrary to previous reports, the rat does not exhibit an important species difference in the response of its renal vasculature to PGE2. Therefore, physiological and pathophysiological roles which have previously been attributed to vasoconstriction produced by PGE2 synthesized in the kidney may now have to be considered.